2004
DOI: 10.3354/meps283293
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of distant marginal ice zones by king penguins during winter

Abstract: We investigated the use of Antarctic waters by king penguins in a 2 yr study based on the satellite tracking of 10 penguins from the Crozet Islands (SW Indian Ocean). All the penguins travelled towards the pack ice, with 3 of them ending their journey at the edge between the marginal ice and the dense pack ice. The mean maximum foraging range and minimal distance travelled were 1620 and 4095 km, respectively. The effect of the satellite transmitter (PTT) attachment on foraging trip duration and colony attendan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 25 publications
3
45
0
Order By: Relevance
“…However, the greater tendency of instrument carriers to make trips in excess of 40 h raises the possibility that birds encumbered by satellite trackers may need to carry out long trips more frequently to maintain body condition than do birds not carrying instruments. This corresponds with the findings of Watanuki et al (1992), Hull (1997) and Bost et al (2004), who observed that instrument effects were most pronounced at times of year when foraging penguins are most energetically stressed.…”
Section: Instrument Effectssupporting
confidence: 53%
“…However, the greater tendency of instrument carriers to make trips in excess of 40 h raises the possibility that birds encumbered by satellite trackers may need to carry out long trips more frequently to maintain body condition than do birds not carrying instruments. This corresponds with the findings of Watanuki et al (1992), Hull (1997) and Bost et al (2004), who observed that instrument effects were most pronounced at times of year when foraging penguins are most energetically stressed.…”
Section: Instrument Effectssupporting
confidence: 53%
“…For long-term experiments on adult penguins, in which the tags were not recovered, there is little speculation or conclusions about the reasons for tag transmission loss. However, data show that losses are high for king penguins, A. patagonicus, traveling in pack ice during the winter [8,9]. Most other experiments have focused on juvenile emperor penguins immediately after fledging, with the hope of tracking them as long as possible through their first year of independence.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining foraging ecology during the non-breeding periods are less common, despite recognition that foraging grounds during the non-breeding period may contain high densities of competitors (e.g., Karnovsky et al 2007). The miniaturization of animal-borne loggers has significantly improved the ability to track the long-distance movements of seabirds during the non-breeding season (e.g., Kooyman et al 2000, Clarke et al 2003, Bost et al 2004, Shaffer et al 2006, Quillfeldt et al 2012). In addition, advances in the use of stable isotope analysis (SIA), which is based on the principle that animals ''are what and where they eat'' Bearhop 2008, Bond andJones 2009), now provide the ability to estimate foraging niches from tissues grown during the nonbreeding period when individuals are away from land (e.g., Polito et al 2011a).…”
Section: Introductionmentioning
confidence: 99%